PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA DINAS KOPERASI DAN USAHA MIKRO KECIL MENENGAH (UMKM) KABUPATEN CIREBON - Asep Sumarsana; Iis Trisnawati; Imas Mufti; Saryadi (PT. Berkah Digital Teknologi, 2024)
The purpose of this study was to determine the organizational culture of the work of employee performance in the Departement of Cooperatives and Micro Small Medium Enterprises Cirebon District. Sampling in this study were all employees of the supervisory and customs and excise service office types of customs cirebon taken as many as 31 respondents. Determination of the number of samples from the study population is done by the technique